Improving students' concept mastery and computational thinking using simulation-driven collaborative problem-solving intervention - Vaflor, Rodel N. (College of Education, University of the Philippines Diliman, 2020)
This study reports on the effects of a simulations-driven Collaborative Problem Solving approach on the concept mastery, computational thinking skills, and collaborative problem-solving processes of Science Technology, Engineering, and Mathematics (STEM) students (N = 82) of a senior high school in Paranaque City. The students concept mastery was measured using the Force concept inventory (FCI) Tool. A I-tailed independent t-test revealed a p-value of .000, which establishes that there is a significance difference in the concept mastery between the CCPS and CPSUS groups, in favor of the latter. Furthermore, the students computational thinking skills were measured using the Computational Thinking Level Scale (CTLS) Tool. A I-talied independent t-test showed a p-value of .018, which signifies a significant difference in the levels of computational thinking skills between the two groups, in favor of the CPSUS. Group. Lastly, a post-dialogue analysis adopted from the 2015 PISA Framework revealed a p-value of .001, which establishes that there is a significant difference in the collaborative problem-solving processes of the two groups, in favor of the CPSUS group. Results from the FCI, CTLS, and dialogue analysis all conclude that the utilization of digital simulations in a collaborative problem-solving environment improves the learners conceptual, computational, and collaborative processes, as compared to a traditional CPS st-up that does not utilize simulations.